Avebury Stone Avenue
With the entry of the Beaker people into England comes a change in architectural attitude. Up to this point the emphasis is on interior space-cells and passages-largely unrelated to exterior form. Now, a passage movement, with a central space, is indicated by avenues and circles of standing stones, as here at Avebury, where the avenue extends for about a mile before entering a circle of over 1,000 ft. in diameter.